1994
DOI: 10.1002/jmri.1880040415
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of regional myocardial ischemia in ex vivo piglet hearts: MR imaging with magnetization transfer

Abstract: The effects of regional myocardial ischemia and reperfusion on magnetization transfer (MT) contrast were investigated in an ex vivo perfused piglet heart model. The extent of the ischemic area was defined with perfusion magnetic resonance (MR) studies performed with use of extracellular contrast agents. Relative MT contrast was calculated for a total of 106 regions of interest in nine hearts. In the areas defined as being severely ischemic in the perfusion studies, a small but significant increase in the MT co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is known that bSSFP signals are influenced by T1, T2 (6), and magnetization transfer effects (7). With increased free water resulting from edema, T1 and T2 are both increased (8) and magnetization transfer is reduced (9). Although T2 and T1 effects are antagonistic in the setting of bSSFP imaging and will work to reduce the overall effect from relaxation changes, the residual relaxational contribution combined with alterations in magnetization transfer (10), it may be possible to visualize reperfused acute myocardial infarct territories as hyperintense zones relative to healthy/remote myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that bSSFP signals are influenced by T1, T2 (6), and magnetization transfer effects (7). With increased free water resulting from edema, T1 and T2 are both increased (8) and magnetization transfer is reduced (9). Although T2 and T1 effects are antagonistic in the setting of bSSFP imaging and will work to reduce the overall effect from relaxation changes, the residual relaxational contribution combined with alterations in magnetization transfer (10), it may be possible to visualize reperfused acute myocardial infarct territories as hyperintense zones relative to healthy/remote myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of other reports addressed tissue characterization, mostly in experimental models. It has been shown that MT affects the signal intensity of myocardium in both acute and chronic infarct (23, 24), as well as in ischemia (25, 26). Furthermore, changes in MT‐weighted images of myocardial tissue were found after heat treatment (27) and in patients with thalassemia (28).…”
mentioning
confidence: 99%